Implementasi Nilai-Nilai Pendidikan Agama Islam Dalam Pembinaan Akhlak Santri Di Pondok Pesantren Darul Amanah Bedono - Laila Fitriatuz; Tsanimaeda Nur; Saiful Hadi; Ahmad Mustafidin (BAMALA Institute, 2025)
This study aims to explore the implementation of Islamic religious education values in the moral development of students at Pondok Pesantren Darul Amanah Bedono. Morality is a crucial aspect of Islamic education that reflects a person's faith and piety. Islamic boarding schools (pesantren) serve as central institutions for shaping students' character through a holistic, integrative, and continuous approach. This research employs a descriptive qualitative method through observation, interviews, and documentation. The findings indicate that the implementation of Islamic values at Pondok Pesantren Darul Amanah Bedono is carried out through habitual worship practices, exemplary behavior from teachers and caregivers, strengthening of religious curriculum, and spiritually-based extracurricular activities. Students' moral development is nurtured through discipline, affection, and a deeply spiritual environment in daily life.